Proverbial and Anti-proverbial Pictures of the World: Based on English and Georgian Anti-Proverbs (European Journal of Education, 2018)
In contemporary paremiology anti-proverb research is experiencing a boom. A great number of scientific papers on the issue have been written by W. Mieder, A. Litovkina, N. Norrick, D. Zaikauskiene, M. Hanzen, N. Can, V. Pavlovic and many others. Anti-proverbs of different languages (English, German, Serbian, Hungarian, Russian, etc.) are studied from different angles: scientists have studied the semantic, structural and stylistic peculiarities of anti-proverbs, various types of transformations in anti-proverbs, the satirical-humorous nature of anti-proverbs, the status of anti-proverbs, the cross-cultural structure of anti-proverbs. Proverbs form proverbial picture of the world, while Anti-proverbs form an anti-proverbial picture of the world. Anti-proverbs show modern mentality of cultures. The present study aims to compare proverbial and anti-proverbial pictures of the world of English and Georgian languages and see the changes in mentality and world vision. The methods used by the researchers in the article are the following: descriptive and comparative methods. The analysis of English traditional proverbs and their transformations showed that the change in life conditions is the reason of semantic changes in anti-proverbs. Contradictory ideas between traditional and anti-proverbs are verbally expressed with antithesis, antonymous words and rhetorical questions. Anti-proverbs show that the truth of traditional proverb is ridiculous in Modern World. As for Georgian anti-proverbs, they did not change the semantics so much as English ones. In Georgian anti-proverbs, words of traditional proverbs are altered by some other words, but the proverbs retain their original meaning. Georgian anti-proverbs are transformations of old ones where certain words change with the change of context.